Prevalence and associated factors of depression and anxiety among Sudanese refugees at Bambasi Camp in northwest Ethiopia: a cross-sectional study - Amede, Endris Seid; Tesfaye, Elias; Ahmed, Gutema (Frontiers in Psychiatry, 2024)
BackgroundRefugees encounter a variety of traumatic events throughout their migratory process and in the camp, which increase their risk of developing mental illnesses. Even though depression and anxiety are the most frequent after a stressful life event, there is limited information on Sudanese refugees. Therefore, this study aimed to assess the prevalence and associated factors of depressive and anxiety symptoms at the Bambasi Camp in northwestern Ethiopia.MethodA cross-sectional study was conducted among 379 participants using a systematic random sampling method. The Hopkins Symptoms Checklist (HSCL-25) was used to assess depressive and anxiety symptoms. The data was collected by the Kobo toolbox mobile application and analyzed using SPSS (version 26). Multiple logistic regressions with the backward elimination method were performed. A p-value of <0.05 with 95% CI was taken as statistically significant.ResultA total of 379 participants were included, with 96.9% response rate. The prevalence of depressive and anxiety symptoms was 46.2% (95% CI = 41–51.2) and 39.6% (95% CI = 34–41), respectively. A multivariable logistic regression analysis indicated that being a female (AOR = 2.56; 95% CI = 1.50–4.26), duration of stay (≥11 years) in the camp (AOR = 2.32; 95% CI = 1.39–3.86), being jobless (AOR = 2.68; 95% CI = 1.30–5.50), and poor social support (AOR = 3.12; 95% CI = 1.25–7.79) were identified as risk factors of depressive symptoms and also being female (AOR = 3.60; 95% CI = 2.26–5.74) and age above 45 (AOR = 2.48; 95% CI = 1.16–5.30) were identified as risk factors for anxiety symptoms.ConclusionThe findings highlight the high burden of mental health problems that Sudanese refugees bear. The identified predictors of depressive and anxiety symptoms should alert medical and refugee professionals to identify vulnerable individuals and groups, to link them to appropriate psychological intervention, and also to take action for the identified risk factors.